2015
DOI: 10.1007/s11121-015-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Moderates the Association Between Proximal Negative Affect and Intimate Partner Violence Perpetration

Abstract: Negative affect is a central component of many theories of aggressive behavior. Though understudied, it is likely that proximal negative affect increases the odds of aggression perpetration when individuals have poor emotion regulation, but not when individuals have more adaptive emotion regulation. Thus, the current study examined (1) the proximal effect of various indicators of negative affect (e.g., anger, hostility, depression) on intimate partner violence (IPV) perpetration and (2) whether poor emotion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 31 publications
9
75
1
1
Order By: Relevance
“…Further, in contrast to predictions, increased alcohol use and heavy use were more strongly associated with increased sexual 1 Although previous research demonstrates that negative affect and emotion regulation interact to predict dating violence in this sample (Shorey et al, 2015), the effects reported in this article remained significant when those interactive effects were controlled for. 2 We also conducted analyses with a contrast between no alcohol use and alcohol use, and a contrast between any alcohol use and heavy alcohol use simultaneously.…”
Section: Discussioncontrasting
confidence: 89%
“…Further, in contrast to predictions, increased alcohol use and heavy use were more strongly associated with increased sexual 1 Although previous research demonstrates that negative affect and emotion regulation interact to predict dating violence in this sample (Shorey et al, 2015), the effects reported in this article remained significant when those interactive effects were controlled for. 2 We also conducted analyses with a contrast between no alcohol use and alcohol use, and a contrast between any alcohol use and heavy alcohol use simultaneously.…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, the strength of the association between deficits in actor emotion regulation (an individual difference factor) and physical IPA may depend upon a partner's level of problematic drinking (a situational factor). Collectively, these findings are consistent with recent research, which found that proximal negative affect was associated with an increased likelihood of IPA among persons with poorer emotion regulation skills as well as numerous studies that suggest affect regulation is a critical predictor of IPA perpetration . Together, these data support prior calls for interventions that promote perpetrators' adaptive emotion regulation skills .…”
Section: Discussionsupporting
confidence: 89%
“…NA is defined as the extent to which a person reports feeling upset or unpleasantly aroused (Watson & Tellegen, ). The literature has revealed how higher levels of NA are related to higher aggression throughout the life span as well as in clinical and nonclinical populations (Chester, Merwin, & Dewall, ; Ebesutani, Kim, & Young, ; Fettich, Mccloskey, Look, & Coccaro, ; Megías, Gómez‐Leal, Gutiérrez‐Cobo, Cabello, & Fernández‐Berrocal, 2018; Shorey, McNulty, Moore, & Stuart, ). NA should be included at the second stage of the GAM as an individual negative internal state that can be influenced by the situational (or personal) variables of Stage 1 (e.g., exposure to violence; Ebesutani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Putting together the EI and NA factors within the GAM, an individual in a specific social situation may incorrectly perceive (perceiving emotion branch) the intentions of an individual to be negative and, consequently, increase his/her NA (e.g., feeling upset) (García‐Sancho, Salguero, & Fernández‐Berrocal, ). This NA could then lead him/her to make an aggressive decision, unless he/she has a high ability to manage their emotions and, therefore, control them (Shorey et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation